Light and scanning electron microscopic studies on the nasopharyngeal - Kumar, Parveen; Kumar, Pawan; Kumar, Suraj (The Indian Journal of Animal Sciences, 2011)
Nasopharyngeal tonsil studied in young healthy goats (15) light and scanning electron microscopy revealed pseudostratified columnar ciliated epithelium with goblet cells and 8-14 rows of oval to elongated nuclei. This respiratory epithelium at places was modified into follicular associated epithelium with characteristic reduced epithelial height, infiltration of lymphocytes, absence ofcilia and the goblet cells. The lamina propria submucosa had lymphoid follicles with characteristic darkly stained corona toward the epithelium. The lymphoid follicles were separated from each other by interfollicular areas displaying collagen and reticular fibres. High endothelial venules were observed toward parafollicular areas. Scanning electron microscopy showed presence of tufts of cilia along with a few goblet cells and islands of microvillus cells which were categorized into different types on the basis ofsurface features ofthe microvilli. Mcells with least number were observed in the follicular associated epithelium.